1974
DOI: 10.1104/pp.53.4.663
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Phosphorus and Water Passage Across Intact Roots by Polyethylene Glycol and Phenylmercuric Acetate

Abstract: The osmotic agent polyethylene glycol and the stomate regulator phenylmercuric acetate have been routinely used to affect the water economy of experimental plants. One or both of these compounds have, however, also been observed to alter plant growth (2,8,10), nutrition (3, 6), photosynthesis (11, 13), and various physical characteristics of the plant (6, 9, 10, 11). Enumeration of such effects is necessary to a critical evaluation of the chemicals. Helpful too would be information on whether the chemicals int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

1977
1977
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…The membrane (Spectrapor 1) had a minimum molecular weight cutoff that excluded the PEG 20M. (3,10,11), and the 02 content of nutrient solutions (9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The membrane (Spectrapor 1) had a minimum molecular weight cutoff that excluded the PEG 20M. (3,10,11), and the 02 content of nutrient solutions (9).…”
Section: Introductionmentioning
confidence: 99%
“…The membrane (Spectrapor 1) had a minimum molecular weight cutoff that excluded the PEG 20M. (3,10,11), and the 02 content of nutrient solutions (9).Zur (15) showed that it was not necessary to place a plant directly into a PEG solution to control its water potential. He (15) and subsequent investigators (2, 4, 16) encased soil-grown plants within semipermeable membranes which were immersed within nutrient solutions containing an osmotic agent (PEG).…”
mentioning
confidence: 99%
“…It was suggested by Lawlor (12) that PEG blocks water pathway and thus induces desiccation. Toxic effects of PEG were attributed to inhibited phosphorus transport across the root to the xylem (2). Others (21,24), however, claimed that PEG may be contaminated with phosphorus, so that high phosphorus concentrations in nutrient solution lead to high rates of uptake.…”
mentioning
confidence: 99%
“…Although such contaminants can be removed by ion exchange resins, gel filtration, or dialysis, toxicity was not always prevented (3,12,18,21). Plant roots are probably not completely impermeable to PEG, and its toxicity might be due to uptake (2,17,21) and translocation throughout the plant (9, 11, 12). Some investigators (11,12,17) claim that it is transported without being broken down and that molecular size will determine the rate of its transport and location (8,9,12 …”
mentioning
confidence: 99%
“…Recent osmotic techniques have favored the use of PEG3 as an osmoticum (1 1,12,14,18). However, a measurable amount of PEG may be absorbed by the plant (1 1,14), and PEG has been reported to reduce phosphorous uptake (7,21,22), translocation (22), and the oxygen content of nutrient solutions (16). These difficulties have been partially overcome by separating the roots from the osmoticum with a semipermeable membrane enclosing a combination of roots and soil (5,8,28,29), or other rooting medium (26).…”
mentioning
confidence: 99%